Preclinical platforms to study therapeutic efficacy of human γδ T cells - Ou, Lingling; Wang, Huaishan; Huang, Hui; Zhou, Zhiyan; Lin, Qiang; Guo, Yeye; Mitchell, Tara; Huang, Alexander C.; Karakousis, Giorgos; Schuchter, Lynn; Amaravadi, Ravi; Guo, Wei; et al. (Clinical and translational medicine, 2022)
Background Gamma delta (γδ) T lymphocytes are promising candidate for adoptive T cell therapy, however, their treatment efficacy is not satisfactory. Vδ2 T cells are unique to primates and few suitable models are available to assay their anti‐tumour function. Methods We tested human γδ T cell activation, tumour infiltration, and tumour‐killing in four three‐dimensional (3D) models, including unicellular, bicellular and multicellular melanoma spheroids, and patient‐derived melanoma organoids. We studied the effects of checkpoint inhibitors on γδ T cells and performed a small molecule screen using these platforms. Results γδ T cells rapidly responded to melanoma cells and infiltrated melanoma spheroids better than αβ T cells in PBMCs. Cancer‐associated fibroblasts (CAFs) in bicellular spheroids, stroma cells in multicellular melanoma spheroids and inhibitory immune cells in organoids significantly inhibited immune cell infiltrates including γδ T cells and lessened their cytotoxicity to tumour cells. Tumour‐infiltrating γδ T cells showed exhausted immunophenotypes with high checkpoints expression (CTLA‐4, PD‐1 and PD‐L1). Immune checkpoint inhibitors increased γδ T cell infiltration of 3D models and killing of melanoma cells in all four 3D models. Our small molecule screen assay and subsequent mechanistic studies demonstrated that epigenetic modifiers enhanced the chemotaxis and cytotoxicity of γδ T cells through upregulating MICA/B, inhibiting HDAC6/7 pathway and downregulating the levels of PD‐L1 and PD‐L2 in CAFs and tumour cells. These compounds increased CXCR4 and CD107a expression, IFN‐γ production and decreased PD‐1 expression of γδ T cells. Conclusions Tumour‐infiltrating γδ T cells show exhausted immunophenotypes and limited anti‐tumour capacity in melanoma 3D models. Checkpoint inhibitors and epigenetic modifiers enhance anti‐tumour functions of γδ T cells. These four 3D models provided valuable preclinical platforms to test γδ T cell functions for immunotherapy. The immunosuppressive TME of these 3D models contained of tumour cells, CAFs and immune cells accompanied by high expression of PD‐L1, PD‐L2 and reduced expression of MICA/B. The immune checkpoint inhibitors and epigenetic modifiers enhance the efficacy of γδ T cells against 3D models. These four 3D models provided valuable preclinical platforms to test γδ T cell functions for immunotherapy.